Pan-tumor genomic biomarkers for PD-1 checkpoint blockade-based immunotherapy - Cristescu, Razvan; Mogg, Robin; Ayers, Mark; Albright, Andrew; Murphy, Erin; Yearley, Jennifer; Sher, Xinwei; Liu, Xiao Qiao; Lu, Hongchao; Nebozhyn, Michael; Zhang, Chunsheng; Lunceford, Jared K; et al. (Science (American Association for the Advancement of Science), 2018)
Programmed cell death protein-1 (PD-1) and programmed cell death ligand-1 (PD-L1) checkpoint blockade immunotherapy elicits durable antitumor effects in multiple cancers, yet not all patients respond. We report the evaluation of >300 patient samples across 22 tumor types from four KEYNOTE clinical trials. Tumor mutational burden (TMB) and a T cell-inflamed gene expression profile (GEP) exhibited joint predictive utility in identifying responders and nonresponders to the PD-1 antibody pembrolizumab. TMB and GEP were independently predictive of response and demonstrated low correlation, suggesting that they capture distinct features of neoantigenicity and T cell activation. Analysis of The Cancer Genome Atlas database showed TMB and GEP to have a low correlation, and analysis by joint stratification revealed biomarker-defined patterns of targetable-resistance biology. These biomarkers may have utility in clinical trial design by guiding rational selection of anti-PD-1 monotherapy and combination immunotherapy regimens.